1975
DOI: 10.1210/jcem-41-6-1161
|View full text |Cite
|
Sign up to set email alerts
|

Klinefelter's Syndrome: Examination of Thyroid Function, and the TSH and PRL Responses to Thyrotropin-Releasing Hormone Prior to and after Testosterone Administration

Abstract: Thyroid function and prolactin (PRL) responsiveness to thyrotropin-releasing hormone (TRH) were examined in 6 patients with Klinefelter's syndrome prior to and after therapy with testosterone. The thyroid function tests, including serum triiodothyronine (T3), thyroxine (T4), thyroxine binding globulin (TBG), resin T3 uptake (RT3U), radioactive iodine uptake (RAIU), thyrotropin (TSH) stimulation and the TSH response to TRH were normal during both periods of study. Testosterone treatment had no significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
(32 reference statements)
4
16
0
Order By: Relevance
“…In fact, when serum testosterone levels dropped to minimal val ues TSH secretion remained unchanged. These data are in keeping with those studies in which testosterone administration was un able to affect TSH secretion in patients with Klinefelter's syndrome [2], Conversely, there are also some reports in which, after testos terone administration to hypogonadal men, an increased [14] or blunted [11] pituitary response to TRH was observed. These dis crepancies may depend on different doses and pharmacological types of testosterone employed or on pretreatment testicular func tion of studied patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, when serum testosterone levels dropped to minimal val ues TSH secretion remained unchanged. These data are in keeping with those studies in which testosterone administration was un able to affect TSH secretion in patients with Klinefelter's syndrome [2], Conversely, there are also some reports in which, after testos terone administration to hypogonadal men, an increased [14] or blunted [11] pituitary response to TRH was observed. These dis crepancies may depend on different doses and pharmacological types of testosterone employed or on pretreatment testicular func tion of studied patients.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the lower TSH response to TRH in males can be ascribed either to low serum estrogen levels [5] or to high serum androgen levels [11]. Testosterone adminis tration inconsistently induces changes in the pituitary TSH response to TRH stimulation in hypogonadal male patients [2,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Burman and cols. (14), showed that testosterone treatment had no significant effect on any of thyroid parameters in the patients with the Klinefelter's syndrome. On the contrary, Morley and cols.…”
Section: Discussionmentioning
confidence: 96%
“…Androgen replacement treatment (testosterone or gonadotropin treatment) have been used to in these patients (2). There was limited data about the effects of sex hormones and hCG on thyroid functions and thyroid volume among hypogonadal male patients (14,(16)(17)(18). Spitz and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in testosterone binding globulin (TeBG) have also been documented (Leroith et al 1981c). Several groups have assessed the effect of exogenous testosterone on PRL and TSH secretion in these patients (Burman, Dimond, Noel, Earll, Frantz and Wartofsky 1975;Cheikh, Hamilton, Hsu and Wiswell 1975;Smals, Kloppenborg, Lequin, Beex, Ross and Benraad 1977). In view of the fact that testosterone can be aromatized to estradiol or reduced to dihydrotestosterone (Nolin, Campbell, Nansel and Bogdanove 1977), the interpretation of these results is difficult because it is not possible to conclude which hormone is producing the effect.…”
Section: Introductionmentioning
confidence: 99%